Preparation and Characterization of Edible Carboxymethyl Cellulose Films Treated by Gamma Irradiation (Journal of Nuclear Technology in Applied Science, 2026)
This study aimed to develop and optimize edible food packaging films based on a  carboxymethyl cellulose (CMC) and glycerol (Glyc) bioblend by utilizing gamma  irradiation as a modification technique. CMC/Glyc films were fabricated via the  solvent casting method and subsequently exposed to low-dose gamma irradiation  (0, 1, 2, and 3 kGy). The resulting films were characterized using Fourier Transform Infrared (FTIR) spectroscopy, mechanical testing (Tensile Strength  and Elongation at Break), and comprehensive thermal analyses, including  Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC),  and Thermomechanical Analysis (TMA). Additionally, barrier properties were  evaluated through Water Vapor Transmission Rate (WVTR) and gas (O2 and  CO2) transmission rates. The results demonstrated that low-dose irradiation (up  to 3 kGy) significantly enhanced the functional properties of the films. Tensile  strength increased from 32.33 MPa at 0 kGy to 34.24 MPa at 3 kGy, alongside  a slight improvement in elongation. Irradiation promoted molecular cross linking, which led to a denser polymer matrix, effectively reducing WVTR and  gas permeability for both O2 and CO2. Thermal stability was also improved, with  irradiated samples exhibiting higher residual char at 491°C compared to the  control. Furthermore, optical transparency increased with the irradiation dose,  reaching a maximum value of 2.79 at 3 kGy.
Keywords: Carboxymethyl cellulose; Gamma irradiation; Edible films; Thermal analysis; Gas barrier properties; Food packaging